1972
DOI: 10.1111/j.1471-4159.1972.tb05118.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of a New Myelin Protein Component

Abstract: A new protein component has been demonstrated in myelin isolated from rat whole brain and from white matter dissected from bovine, dog and rabbit brain. It is also present in rabbit optic nerve. It does not appear to be present in other subcellular fractions of rat brain. It has a molecular weight of 20,540 ± 490(S.D.), as determined by polyacrylamide gel electrophoresis in sodium dodecyl sulphate. A rapid procedure for the isolation of myelin is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(88 citation statements)
references
References 24 publications
3
85
0
Order By: Relevance
“…These studies indicated the homogeneity and purity of our samples. The electrophoretic profiles were similar to those reported by Agrawal et al (1972) except that the DM-20 band was not detectable in our myelin preparations. Only faint bands corresponding to basic protein and proteolipid protein were detectable in the myelinlike preparation (Plate 3).…”
Section: Characterization Ofmyelin and Myelin-likefractionssupporting
confidence: 88%
See 1 more Smart Citation
“…These studies indicated the homogeneity and purity of our samples. The electrophoretic profiles were similar to those reported by Agrawal et al (1972) except that the DM-20 band was not detectable in our myelin preparations. Only faint bands corresponding to basic protein and proteolipid protein were detectable in the myelinlike preparation (Plate 3).…”
Section: Characterization Ofmyelin and Myelin-likefractionssupporting
confidence: 88%
“…Disc-gel electrophoresis in sodium dodecyl sulphate was carried out essentially as described by Agrawal et al (1972 washed three times with water by centrifugation and all the supernatants were combined, dialysed at 2°C against 0.1 M-acetic acid for 2 days and freezedried. Proteolipid protein and high-molecular-weight (Wolfgram, 1966) protein.…”
Section: Other Methodsmentioning
confidence: 99%
“…They are translated from four different mRNAs (50), and the four MBP mRNAs can be produced from a single MBP gene by alternative mRNA splicing (12,44). Two PLPs are present in myelin, the major PLP, which has an apparent molecular weight of 25,000, and the closely related proteolipid DM20 (1), which has an apparent molecular weight of 20,000. PLP and DM20 may have a relationship similar to that found among the four MBPs, since they have identical amino-and carboxyl-terminal sequences (46), and they are very closely related by amino acid composition and by antigenic characteristics.…”
mentioning
confidence: 99%
“…The paradox regarding the proteolipid nature of MBP is widely known but largely ignored (Agrawal et al, 1972; (Table III), has physical significance.…”
Section: Discussionmentioning
confidence: 99%